Kepemimpinan Trasnformasional Kepala Sekolah Penggerak dalam Mendorong Implementasi Aktualisasi Diri Peserta Didik (Studi Multi Situs di SMAN 1 Masbagik dan SMAN 1 Selong) - Ahmad Nizar Hasim; Nurul Yakin; Subki Subki (LP2M STIT Palapa Nusantara, 2023)
This study aims to determine the role of transformational leadership of school principals in encouraging the implementation of students' self-actualization. This study uses a descriptive qualitative approach with multi-site types. Data was collected by non-participant observation, in-depth interviews, and documentation. Data analysis was carried out by summarizing, presenting data, drawing conclusions, and verifying the temporary nature. The research location was at SMAN 1 Masbagik and SMAN 1 Selong. The research was conducted for 13 weeks starting from September to December 2022. The results of this study indicate that the transformational leadership of the driving school principal has a very important role in encouraging the implementation of student actualization. The transformative leadership model for driving school principals is carried out through the establishment of an Education Unit Operational Curriculum (KOSP) committee, an assessment team consisting of diagnostic assessment, formative assessment (daily), and summative assessment (semester), and the Project Team for Strengthening Pancasila Student Profiles (P5, teacher training). The expert then disseminates it to other teachers. Strengthening the character of students according to the Pancasila Student Profile is carried out through school engineering in extracurricular, intra-curricular, co-curricular, and school culture activities. The difference in the role of the two principals lies in the form of handling of the principal in dealing with incoming teacher indiscipline The principal of SMAN 1 Masbagik tends to apply preventive measures and avoids repressive actions. The preventive form of the principal of SMAN 1 Masbagik is carried out as a family. Meanwhile, the principal of SMAN 1 Selong takes preventive and repressive measures to ensure that children get excellent service and keep other decisions to be carried out by regulations that have been determined together. Thus it can be concluded that the transformational leadership of the driving school principal at SMAN 1 Masbagik and SMAN 1 Selong has a role in encouraging the implementation of students' self-actualization.